(untitled) - Sears, Francis Weston (Reading, Mass., 1960)
This text develops problem-solving skills. It also: emphasizes conceptual understanding, reinforced by examples; includes applications; and features a treatment that focuses on the essential core material.
Keywords: Physics,Vật lý